Origin of sucrose metabolism in higher plants: When, how and why? - Salerno, Graciela Lidia (2003)
Since the discovery of sucrose biosynthesis, considerable advances have been made in understanding its regulation and crucial role in the functional biology of plants. However, important aspects of this metabolism are still an enigma. Studies in cyanobacteria and the publication of the sequences of several complete genomes have recently significantly increased our knowledge of the structures of proteins involved in sucrose metabolism and given us new insights into their origin and further evolution.